Favorable long-term outcomes of endoscopic submucosal dissection for locally recurrent early gastric cancer after endoscopic resection - Sekiguchi, Masau; Suzuki, Haruhisa; Oda, Ichiro; Abe, Seiichiro; Nonaka, Satoru; Yoshinaga, Shigetaka; Taniguchi, Hirokazu; Sekine, Shigeki; Kushima, Ryoji; Saito, Yutaka (Endoscopy, 2013)
Background and study aim: Close observation after noncurative endoscopic resection for early gastric cancer (EGC) is an acceptable option if a positive horizontal margin or piecemeal resection of differentiated-type adenocarcinoma is the only noncurative factor. When locally recurrent EGC is subsequently detected, endoscopic submucosal dissection (ESD) may be performed, although only limited research has been reported regarding the outcomes. We aimed to evaluate the effectiveness, safety, and long-term clinical outcomes of ESD performed for locally recurrent EGC.Patients and methods: Endoscopic resection was performed in 3704 patients with a total of 4216 EGC lesions between January 1997 and December 2011 at our institution. During this period, 95 patients with 95 locally recurrent EGCs following their endoscopic resection underwent ESD performed by experts, which we retrospectively reviewed. The prior endoscopic resection procedures were endoscopic mucosal resection in 75 cases and ESD in 20.Results: Of the 95 cases, en bloc resection was achieved in 90.5 %, R0 resection in 84.2 %, and curative resection in 81.1 %. Median procedure time was 70 minutes; no bleeding requiring blood transfusion was seen. There were six perforations (6.3 %), with one necessitating emergency surgery. Within a median follow-up period of 76.4 months (range, 10.5 – 170.0 months), second local recurrences occurred in three patients. Five-year overall and disease-specific survival rates were 92.8 % and 100 %, respectively.Conclusions: ESD was safe and effective with favorable long-term clinical outcomes for locally recurrent EGC following endoscopic resection.